Kenali loghat Pulau Pinang (V1) / Azlina Mohd Mydin ... [et al.] - Mohd Mydin, Azlina; Wan Mohammad, Wan Anisha; Mohamed Yusoff, Syarifah Adilah; Johan, Elly Johana (Unit Penerbitan dan Publisiti JSKM, 2022)
Cheq - saya Hampa - korang Depa - diaorang Awat - kenapa Habaq - beritahu Bang - azan